Two Early Romanesque Fragments of Church Furnishings Found in the Square Tower of the Tnin Fortress (Archaeologia Adriatica, 2010)
The article analyzes two newly discovered original early Romanesque fragments of a pilaster that was long ago reconstructed by Gunjača on the basis of two original pieces, while the other two were replaced. During structural repairs and conservation at the fortress of Tnin in Knin in 2006, the missing two original segments were discovered, which Gunjača had though had been forever lost. They consist of the central part of the pilaster and the base. The fragments are analyzed in catalogue form. In addition to the analysis of the two newly found fragments, other fragments discovered earlier that also have early Romanesque characteristics were also considered. In contrast to the majority of earlier known examples that have an inscription field, fragments are analyzed here that have a characteristic decoration that ties them to the previously noted finds. Through a method of comparison, stylistic decorative traits are noted that characterize one and the other fragment on the kymation. The comparisons were carried out not merely on the early Romanesque fragments from the Knin fortress, but also from the site of Kapitul, and further on one fragment of an architrave beam whose provenience is not known, currently located in the Archaeological Museum in Split. As it has the same stylistic decorative characteristics as the two new Romanesque fragments from Knin, a three-braided ribbon and stylized flowers, it probably came from the same workshop circle or even the same ecclesiastical structure, the Church of St. Stephen in Knin. As arched elements that come from Kapitul are also located in the Archaeological Museum in Split, it is not excluded that several fragments that are kept in the that museum come from the Knin region. The analysis carried out on the two new early Romanesque pilaster fragments has led to results tied to the question of the stonemasonry workshops, or workshop circle in which the carving took place. The emphasis on a workshop circle in Knin again becomes topical, and explanations offered by earlier researchers for this Knin workshop find their confirmation in the discovery of these two new early Romanesque fragments. It can be concluded that the investigation into the past of Knin becomes more interesting everyday in archaeological terms, as it once was long before. This refers primarily to the area of Podgrađa (the suburbium), where excavations have been performed for several years, as well as the Knin fortress itself. The results of such investigation, as well as the conservation works following structural repairs that have been carried out at the Knin fortress for a long time at the northern fortress of Tnin, are particularly valuable, as they are one of the indicators of the development of the medieval city, as indicated by the discovered material, as well as the stone furnishings. Similarly, in this case the confirmation of the existence of an ecclesiastical structure has acquired full meaning though the identification of its interior stone inventory.
Keywords: mediaeval Knin; pilaster; kymation; three-braided ribbon; Romanesque stonemasonry workshop; church of St. Stephen